St. Vincent - Melfi, Theodore; Chernin, Peter, 1951-; Topping, Jenno; Roos, Fred; Murray, Bill, 1950 September 21-; McCarthy, Melissa, 1969-; Watts, Naomi, 1968-; O'Dowd, Chris, 1980-; Howard, Terrence; Lieberher, Jaeden; Weinstein Company; Chernin Entertainment; et al. (Beverly Hills, CA : Anchor Bay Entertainment, 2015)
Maggie, a single mother, moves into a new home in Brooklyn with her twelve-year old son, Oliver. Forced to work long hours, she has no choice but to leave Oliver in the care of their new neighbor, Vincent, a retired curmudgeon with a desire for alcohol and gambling. An odd friendship soon blossoms between the improbable pair. Together with a pregnant stripper, named Daka, Vincent brings Oliver along on all the stops that make up his daily routine, race track, strip club, and a dive bar.
DVD, NTSC region 1, anamorphic widescreen (1.78:1) presentation; Dolby Digital 5.1 surround.
In English, dubbed Spanish, or dubbed French; Spanish subtitles; English subtitles for the deaf and hard-of-hearing (SDH).
Title from disc surface.
Bill Murray, Melissa McCarthy, Naomi Watts, Chris O'Dowd, Terrence Howard, Jaeden Lieberher.
Music, Theodore Shapiro ; editor, Peter Teschner, Sarah Flack ; production designer, Inbal Weinberg ; director of photography, John Lindley.
Originally released as a motion picture in 2014.
Keywords: Single mothers -- Drama; Neighbors -- Drama; Retirees -- Conduct of life -- Drama; Babysitters -- Drama; Brooklyn (New York, N.Y.) -- Drama; Feature films; Comedy films; Video recordings for the hearing impaired